Design of CMOS current-mode multiplier-divider circuit for type-2 FLC applications - Dos Santos, Rodrigo Bispo [UNESP]; Rizol, Paloma M. S. Rocha [UNESP]; Mesquita, Leonardo [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2015)
The design of a low voltage current-mode CMOS multiplier/divider circuit is presented in this paper. This circuit is used to implement the type-reducer block of Type-2 Fuzzy Logic Controller chip. The simulation results of multiplier/divider circuit have been done in CMOS 0.35μm technology through Pspice software using a single supply voltage of 1.8V.
Keywords: Interval type-2 fuzzy logic controller; Multiplier/divider; Type-2 fuzzy logic